Does concrete modular system add value in residential buildings? - Case study and qualitative evaluation. (1st March 2023) - Lim, Jason; Afla, Muhammad Nurul; Oey, Elia
The concept of modularity has been widely accepted in production environment. However, its adoption in the construction sector is still limited. The research aims to address what are the main (sub) challenges in adopting concrete modularity concept in residential housing. The study collected possible challenges from previous studies, and asked expert respondents to perform AHP-pair wise comparison. It also used parameters from two case projects of a two-storey housing to examine the time and cost implications for modular concrete construction. The results shown the 'high upfront investment cost', 'lack of interest from consumers', 'no/lack of guidelines and regulation in design', 'lack of suppliers/products' and 'complexity to integrate with onsite structure' as the top five sub-challenges. From the project case 4% cost increase and 25% time saving can be expected from modular concrete adoption to a two-storey housing project.